Implementation of Risk-Based Audits at the North Sulawesi Provincial Inspectorate: An Ethnographic Study of the Cultural Values of “Si Tou Timou Tumou Tou” - Revina Arini Porong; Heince R.N Wokas; Claudia W.M Korompis (Publikasi Indonesia, 2026)
This study examines the implementation of Risk-Based Internal Audit (RBIA) at the North Sulawesi Provincial Inspectorate and explores how the local cultural values of Si Tou Timou Tumou Tou influence audit practices. Although RBIA has been formally mandated in Indonesia through national regulations, its implementation at the regional government level often remains procedural and has not been fully internalized substantively. This research aims to analyze the implementation of RBIA, identify the internalization of cultural values in audit practices, and explain their influence on auditors’ attitudes, behavior, and decision-making. A qualitative approach with an ethnographic method was employed. Data were collected through participant observation, in-depth interviews with five key informants consisting of senior auditors, junior auditors, structural officials, and technical staff, as well as document analysis. The data were analyzed inductively using data reduction, data display, and conclusion drawing, supported by triangulation and member checking. The findings show that RBIA at the North Sulawesi Provincial Inspectorate has been implemented formally across all audit stages, but substantively remains in a transitional phase due to incomplete risk data, limited technological support, and varying auditor competencies. The cultural values of Si Tou Timou Tumou Tou—particularly togetherness, honesty, social responsibility, and devotion—are internalized in audit practices and foster a more humanistic, dialogic, and constructive approach. However, these values may also create ethical dilemmas related to auditor independence and objectivity. This study contributes theoretically to the development of culturally grounded public sector auditing and offers practical recommendations for strengthening adaptive and sustainable internal supervision systems.